Analysis of Vibration of Roadheader Rotary Table Based on Finite Element Method and Data from Underground Coalmine - Minjun Zhang; Fuyan Lyu; Xiushan Tang; Yang Yang; Xiaodong Ji; Miao Wu (Shock and Vibration)
The intense vibration of a roadheader rotary table damages the cutting system of the roadheader and reduces the efficiency. This paper analyzes the vibration of a rotary table by combining the finite element model with tested data from an underground coalmine. First, the force of the rotary table during the cutting procedure was analyzed, and the finite element model was built using Pro/E and ADAMS. The tested data were then imported into the model after selection, procession, and combination were conducted. Next, the six lowest-order parameters of the rotary table were calculated. A vibration analysis of the rotary table under certain working conditions was conducted, and the results were compared with those from a modal experiment using a single-point excitation method. According to the comparison between the simulation result and experiments, it is clear that this method is both reasonable and feasible. And it could supplement the theoretical foundation of the analysis of other roadheader components, providing reference for the improvement of the structure and dynamic properties of a roadheader. In addition, other vibration components of a roadheader such as the cutting head and the cutting arm could also be analyzed through the proposed method, with very reliable precision.